Reconstructing historical Pb and Hg pollution in NW Spain using multiple cores from the Chao de Lamoso bog (Xistral Mountains) - Martínez Cortizas, Antonio; Cheburkin, Andriy K. (Geochimica et cosmochimica acta, 2012)
We have applied a single-bog multi-core approach to reconstruct historical Pb and Hg accumulation in an ombrotrophic bog from NW Spain, Chao de Lamoso (Xistral Mountains). Mercury was determined using a LECO-ALTEC AMA-254 analyzer, Pb with an EMMA-XRF analyzer and stable lead isotopes (four cores) by Quadrupole ICP-MS. Maximum concentrations were 74-122μgg−1 for Pb and 142-300ngg−1 for Hg. Higher variability was found for Hg than for Pb (2-3 times and 1.5 times, respectively). The slopes of the relationship between Hg and Pb cumulative inventories also suggested differences in relative accumulation of both elements. This substantial spatial variability indicates that, compared with Pb, a more extended sampling may be needed for an accurate estimation of Hg accumulation in mires. The isotopic records showed higher and almost constant 206Pb/207Pb ratios (average 1.174±0.004) in the lower sections and a continuous decrease to the surface (minimum 1.141). By using the change in the isotopic composition of Pb we estimated a chronology for the last ∼200years which enabled and approximation of the temporal trends in metal pollution. Based on the average isotopic composition of the studied cores and the application of a simple binary mixing model, six periods with increasing proportions of pollution Pb were identified: prior to ∼1875 AD, with an average proportion lower than 16%; ∼1875-1910 AD, increasing up to 24%; ∼1910-1950 AD, up to 35%; ∼1950-1970, up to 54%; ∼1970-1980 AD, up to 74%; and after ∼1980 AD, increasing up to 80%. The period with the highest rate of increase in recent (since ∼1900 AD) pollution Pb (equivalent to 2% year−1) seems to have started at the maximum in Pb accumulation around the early 1970s. The Hg records showed a more simple evolution with four main phases: prior to ∼1875 AD with enrichments around 1.5-fold the background, ∼1875-1955 AD with increasing enrichments; from ∼1955 AD to ∼1980 AD with maximum values (up to 4.2-fold); and from ∼1980 AD to present, with a steady decline to 2.4-fold. For the most recent period (after ∼1980 AD), the combination of decreasing Pb and Hg concentrations and accumulation rates/enrichments, and low 206Pb/207Pb ratios, may point to a higher relative importance of local sources (i.e. coal burning in a nearby power plant) in atmospheric metal pollution in the area.
Gesehen am 18.04.2018